Roadmap Concept Increasing The Competence of TNI AL Surveyor Personel With AHP and SWOT Methods - Pompy Pratisna; Iwan Indrawan; Siswanto Siswanto; Eko Arie Kurniawan (Universitas Pamulang, 2022)
One of the defense equipment that determines the readiness of the Navy in maintaining the integrity of the Republic of Indonesia is the Republic of Indonesia Warship (KRI). The worthiness of the KRI is of course the main parameter that is always integrated with the condition that it is always ready to fight to maintain Indonesia's sovereignty at sea . The readiness of the KRI is assessed from the aspect of equipment feasibility as a benchmark to determine the level of readiness and capability of the warship. This research aims to analyze the concept of increasing the competence of the Navy surveyor personnel. The research method used is the AHP and SWOT methods. The results of the study indicate that the appropriate strategy to be applied by the Navy in order to achieve sustainable competitive advantage is by : a ) increasing the competence of the Navy with formal and informal course activities, b ) increasing cooperation with external institutions, c ) increasing standardization socialization. operational test equipment to increase the ability to operate test equipment owned by the Indonesian Navy's airworthiness personnel, d ) add equipment in accordance with the update on the development of defense equipment, and e ) improve the coaching program for both tour of duty and tour of area.